Islamic Moral Education as a Means to Reduce Aggression and Antisocial Behavior In Islamic Elementary School - Rahayu, Evi; Kustati, Martin; Sepriyanti, Nana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2026)
This study explores teachers’ and students’ perspectives on Islamic Moral Education (IME) as a strategy to reduce violence and antisocial behavior among adolescents in Islamic elementary schools. The research was motivated by the increasing need to strengthen moral education as a foundation for emotional regulation and social harmony in educational environments. A mixed-methods approach was employed, combining quantitative and qualitative techniques to obtain a comprehensive understanding of the issue. Quantitative data were collected through a 50-item questionnaire administered to 70 participants, consisting of 10 teachers and 60 students. Qualitative data were obtained through semi-structured interviews with selected participants. Quantitative analysis using SPSS 25 indicated that all dimensions of IME including the integration of Islamic values, behavioral guidance, empathy development, and the influence of teachers and school culture showed significant negative correlations with aggression and antisocial behavior (r = –0.61 to –0.72, p < 0.01). Multiple regression analysis revealed that empathy development was the strongest predictor of behavioral improvement (β = –0.41, p < 0.001). Qualitative findings supported these results, showing that IME promotes self-control, respect, forgiveness, and compassion through moral reflection, Qur’anic teachings, and teacher role modeling. Teachers were perceived as moral exemplars, while regular religious practices such as prayer, reflection, and moral storytelling helped create a supportive ethical climate. However, challenges such as social media influence and limited parental involvement were also identified. The findings suggest that IME plays a significant role in strengthening empathy, emotional regulation, and prosocial behavior among students. Therefore, integrating IME across the school curriculum is recommended, and further research should examine its long-term impact and adaptation to digital educational contexts.